Digital Content Design for Promoting Tourism: A Case Study of Pokdarwis Pandeglang's Instagram - Setiawan, Fathur Rahman Awanissa; Wihardi, Doddy; Jati, Rocky Prasetyo (Transpublika Publisher, 2026)
In the digital age, social media platforms such as Instagram have become essential tools for promoting tourism, particularly in rural areas with limited resources. This study explores the role of digital content design in enhancing the visibility of local tourism destinations, focusing on a collaboration between students of the Communication Science program at Universitas Budi Luhur and the Pokdarwis (Tourism Awareness Group) in Sumberjaya Village, Pandeglang, Banten. The collaboration aimed to develop a digital content strategy for promoting the village’s tourism potential through Instagram. The study employed a combination of content creation, audience analysis, and training workshops to empower local residents with the skills to manage and create their own digital content. The project demonstrated a significant increase in engagement on the village’s Instagram account, with followers rising by 40% and higher interaction rates across posts. Key content types included promotional posts, behind-the-scenes footage of local cultural events, and a